Naknadna vplačila v kapital gospodarskih družb - Kocbek, Marijan (Podjetje in delo, 2019)
The paper examines the long-standing controversial issue of taxation of subsequent payments into capital of companies. The final answer was given by the Supreme Court of the Republic of Slovenia, which decided that subsequent payments should be considered relevant when taxing capital gains. The author welcomes the verdict of the Supreme Court, which saves one of the fundamental corporate legal institutes, which is very important in business practice, especially for limited liability companies. A different decision that would uphold the controversial taxation of subsequent payments would make this institute meaningless. The author presents the legal nature and theoretical concept of subsequent payments and their practical importance for use in business practice, both in establishing companies and in raising capital (not share capital), as well as procedures related to return of subsequent payments.